Navigating Challenges of Italy’s Transnational Education Landscape - Sguaitamatti, Elisa (International Higher Education, 2025)
This article explores Italy’s transnational education perspective and current state of play by analyzing its complex landscape both as a TNE importer (branch campuses, filiations, off-shore campuses, and multinational corporate universities) and TNE exporter (branch campuses and virtual universities). Furthermore, it focuses more closely on the Italian approach in addressing emerging challenges in quality assurance and recognition of such TNE qualifications.